Pelatihan Menyusun Referensi dan Mensitasi Karya Ilmiah dengan Menggunakan Aplikasi Mendeley Reference Manager - Susilawati; Asmalidar; Nurlinda; Barus, Enny Segarahati; Asriyati (Politeknik Negeri Medan, 2024)
This training activity was carried out to improve student competence in completing the Final Report, especially in managing references and citing scientific papers using the Mendeley Reference Manager application. The Elsevier company developed this application, first launched in August 2008. Mendeley is a reference management software that students need to learn. A good final report must include valid reference evidence per applicable regulations. Currently, what happens in writing the Final Report of Medan State Polytechnic students, especially the Accounting Department, is that there are still several mistakes in making the bibliography or not citing the reference sources used in the scientific work; this is due to the lack of student understanding of applications that can be used to facilitate the preparation of the Final Report. Understanding how to write the final report and citing the reference source is very important to help students facilitate the writing of the final report, so it is introduced and trained to students regarding applications that can be used. With the Mendeley reference application that can be used for free, it is hoped that students can apply it in making final reports. The result of this Service Activity is an increase in knowledge, understanding, and proficiency of final-year students of the Accounting Finance and Banking Study Program using Mendeley Reference Manager to write their final report.